Comparison of EZ blocker and left double-lumen endotracheal tube for one lung ventilation in minimally invasive cardiac surgery - Bermede, Onat (Journal of Surgery and Medicine, 2021)
Background/Aim: Effective lung isolation is required in minimally invasive cardiac surgery. Double lumen tubes (DLT) are most preferred for this type of operation, and data on the use of EZ blockers in cardiac surgery are limited. We aimed to compare the efficiency of the double lumen tube and EZ blockers in minimally invasive cardiac surgery with cardiopulmonary bypass performed through a right mini thoracotomy. Methods: A total of 89 patients who underwent minimally invasive cardiac surgery through right mini thoracotomy with cardiopulmonary bypass between January 1 and December 31, 2020, were included in this single-center, retrospective case control study. The group in which double lumen tubes were used for lung isolation (n = 58) was compared with that in which EZ blockers (n = 31) were used in terms of placement time, repositioning rate, lung collapse quality score, and postoperative sore throat and hoarseness. Results: The time needed to place the devices in the correct position was shorter in the DLT group (3.2 (2.7) min vs 4.6 (2.4) min, P=0.02). No significant difference was found between the prevalence of at least one repositioning and lung collapse quality scores (P=0.42, P=0.21). VAS scores for sore throat were lower and hoarseness was less encountered in the EZ blocker group (21.2 (8.8) vs 49.4 (7.6), P=0.01, 16.1% vs 48.2%, P=0.01, respectively). Conclusion: Although the EZ blocker has a longer placement time, it provides lung isolation as effective as DLT. Less sore throat and hoarseness show that EZ blocker is an important alternative for this type of surgery.